2013
DOI: 10.1002/aqc.2388
|View full text |Cite
|
Sign up to set email alerts
|

Fishery benefits from behavioural modification of fishes in periodically harvested fisheries closures

Abstract: Periodically harvested fisheries closures are widely implemented across the South Pacific as a conservation and fisheries management tool. There is a lack of information on the mechanisms and effectiveness of this management system in meeting fisheries and ecosystem sustainability goals.A before‐after‐control‐impact (BACI) pair design, was used to quantify flight initiation distance (FID), and biomass of two fishery‐target (Acanthuridae and Scaridae) and one non‐target (Chaetodontidae) families in two periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 32 publications
6
39
1
Order By: Relevance
“…However, we were not able to account for migration/movement of targeted species across PHC boundaries, which differs among target species (Nash, Welsh, Graham, & Bellwood, ) and is, therefore, likely to have contributed to the variability in results across PHCs (Eggleston & Parsons, ). Regardless of the mechanism, greater abundance and biomass of fish in PHCs translated to harvest benefits where fishers removed an average of 29% of the abundance and 49% of the biomass, a result likely due to greater catch efficiency associated with decreased wariness of targeted fishes within PHCs (Feary et al., ; Goetze, Januchowski‐Hartley et al., ; Januchowski‐Hartley et al., ). Therefore, PHCs are a particularly effective fisheries management strategy for increasing short‐term fisheries yields from single harvest events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we were not able to account for migration/movement of targeted species across PHC boundaries, which differs among target species (Nash, Welsh, Graham, & Bellwood, ) and is, therefore, likely to have contributed to the variability in results across PHCs (Eggleston & Parsons, ). Regardless of the mechanism, greater abundance and biomass of fish in PHCs translated to harvest benefits where fishers removed an average of 29% of the abundance and 49% of the biomass, a result likely due to greater catch efficiency associated with decreased wariness of targeted fishes within PHCs (Feary et al., ; Goetze, Januchowski‐Hartley et al., ; Januchowski‐Hartley et al., ). Therefore, PHCs are a particularly effective fisheries management strategy for increasing short‐term fisheries yields from single harvest events.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, PHCs were implemented to increase catch efficiency through a decrease in fish wariness, because fishers observed that the behaviour of fish changes during closure, making them easier to catch (Cinner, Marnane, McClanahan, & Almany, ; Feary, Cinner, Graham, & Januchowski‐Hartley, ). More recently an increase in catch efficiency within PHCs has been observed for invertebrates harvested via gleaning (collection during low tide) (Cohen & Alexander, ) and fish through a reduction in wariness to spearfishers (Goetze, Januchowski‐Hartley, et al., ; Januchowski‐Hartley, Cinner, & Graham, ). However, this increased catchability also means that a small amount of fishing effort can effectively remove substantial biomass (Jupiter et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional community closures often involve short closure times (i.e., 100 d in Fiji), which may coincide with the time needed to make fish less wary to spearfishers (e.g., Januchowski‐Hartley et al. ), but shorter than the time needed to produce significant increases in abundance, length, or biomass (McClanahan et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…, Januchowski‐Hartley et al. ). Customary closures have been observed to reduce FID to an extent that is likely to increase catchability for surgeonfish (Acanthuridae) within six months of closure, an effect lost in as little as three days when reopened to fishing (Januchowski‐Hartley et al.…”
Section: Introductionmentioning
confidence: 99%